Emotional Support for Diabetes Management: An International Cross-Cultural Study. (June 2015) - Kowitt, Sarah D.; Urlaub, Diana; Guzman-Corrales, Laura; Mayer, Melissa; Ballesteros, Juana; Graffy, Jonathan; Simmons, David; Cummings, Doyle M.; Fisher, Edwin B.
Purpose: The purpose of this study was to explore how emotional support emerged in interactions between peer supporters (PSs) and adults living with type 2 diabetes. Methods: Qualitative data were analyzed from 22 semistructured interviews with PSs in 3 settings: low-income Latinos in Chicago, middle-class Caucasians in the United Kingdom, and low-income African American women in North Carolina. Emotional support was defined as expressions of empathy, trust, and caring. Results: Across all sites, emotional support gradually emerged over time, was often combined with informational support, and was conveyed both implicitly (through nonverbal actions connoting emotional acceptance; eg, a walk together without discussion of problems) and explicitly (eg, by reassurance or discussion of stressors). Cross-site differences did appear regarding the strategies to address barriers to diabetes management (eg, PSs in North Carolina and Chicago reported providing support for social stressors) and the role of PSs (eg, PSs in Chicago reported providing directive support). Conclusions: Across different settings and populations, emotional support for diabetes management evolved over time, was often integrated with informational support, and emerged through both implicit and explicit strategies that addressed varied context-specific stressors.